2019
DOI: 10.5114/jcb.2019.90448
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cervical cancer brachytherapy in India: results of an online survey supported by the Indian Brachytherapy Society

Abstract: Purpose: Cervical cancer is the most common gynecological cancer in India. Uniform protocol-based treatment is important for achieving optimal outcomes. We undertook a survey to investigate patterns of care with special regard to patterns of care in cervical cancer brachytherapy in India. Material and methods: A 17-question online survey was sent to radiation oncologists across India. Respondents were required to have a minimum of 1-year experience. One response per center was accepted and deemed as representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…For CT based planning, dose was prescribed at point A and conventional pear shaped 100% isodose surface was graphically optimized for OAR sparing. This practice of ours is also reflected in an online survey by Indian brachytherapy society done on patterns of cervical cancer brachytherapy in India, published in 2019 ( Chatterjee et al, 2019 ). In this survey, CT imaging was used by two third respondents and despite of availability of CT, point A based dose prescription remained the most common form of prescription (66%).…”
Section: Discussionmentioning
confidence: 53%
“…For CT based planning, dose was prescribed at point A and conventional pear shaped 100% isodose surface was graphically optimized for OAR sparing. This practice of ours is also reflected in an online survey by Indian brachytherapy society done on patterns of cervical cancer brachytherapy in India, published in 2019 ( Chatterjee et al, 2019 ). In this survey, CT imaging was used by two third respondents and despite of availability of CT, point A based dose prescription remained the most common form of prescription (66%).…”
Section: Discussionmentioning
confidence: 53%
“…Though the use of image-adapted brachytherapy is common in high-income countries, the same has not been the case in Asia. In a survey of practice in South East Asia, it was observed that this approach has not yet been initiated in many countries with CT scanners, and the use of MRI for treatment remains implausible 48 49. In addition, the recent increase in replacement of brachytherapy by external beam radiation therapy techniques due to lack of brachytherapy equipment and training limitations has resulted in inferior outcomes 50 51.…”
Section: Latin America and The Caribbeanmentioning
confidence: 99%
“…Even with the advent of 3-D image-based BT, these points are still relevant, as many centres in low-and middle-income countries are still prescribing doses to point A, and studies comparing absorbed doses at ICRU reference points with CT-based treatment planning show that the ICRU rectal point dose correlates well with D2cc [12][13][14].…”
Section: Brachytherapy Procedures and Planningmentioning
confidence: 99%